Galli gigeriae endothelium corneum: its intestinal barrier protective activity in vitro and chemical composition - Shanshan Li; Meng Zheng; Zhentang Zhang; Hengying Peng; Wenling Dai; Jihua Liu (BMC, 2021)
Abstract Background Galli gigeriae endothelium corneum (GGEC) has been effectively used for centuries for the treatment of functional dyspepsia (FD) in clinical practice in Asian countries. However, its potential mechanism and chemical composition remains undertermined. Methods In this study, the chemical profile of GGEC ethyl acetate extract (EAE) was evaluated by HPLC-Q-TOF-MS/MS. The effects of EAE on intestinal barrier function and inflammation were investigated in IEC-6 cells and RAW264.7 cells. Results The results showed that 33 compounds were tentatively identified, including 12 soy isoflavones, 7 bile acids for the first time in EAE. EAE significantly reinforced intestinal barrier function via increasing the tight junction protein levels of ZO-1 and Occludin, reducing the mRNA expression levels of interleukin (IL)-1β and IL-6 in tumor necrosis factor alpha (TNF-α)-challenged IEC-6 cells. The scratch wound assay showed that EAE accelerated wound healing of IEC-6 cells. EAE evidently reduced the level of NO in a dose-dependent manner with an IC50 value of 18.12 μg/mL, and the mRNA expression of TNF-α, IL-1β, IL-6, iNOS and COX-2 in LPS-treated RAW264.7 cells. Conclusion This study revealed the intestinal barrier protective effects and chemical profile of GGEC, and the results indicated that GGEC strengthened the intestinal barrier by up-regulating protein expression of tight junctions and limiting inflammatory responses.